2000
DOI: 10.1136/jnnp.69.1.40
|View full text |Cite
|
Sign up to set email alerts
|

Prospective analysis of bedside percutaneous subdural tapping for the treatment of chronic subdural haematoma in adults

Abstract: Objectives-Although there is general agreement that surgery is the best treatment for chronic subdural haematoma (CSDH), the extent of the surgical intervention is not well defined. Methods-The less invasive surgical technique of bedside percutaneous subdural tapping and spontaneous haematoma efflux after twist drill craniostomy under local anaesthesia was prospectively analysed in 118 adult patients, 99 with unilateral and 19 with bilateral CSDH. Results-The mean number of subdural tappings was 3.2. Ninety tw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
66
2
16

Year Published

2006
2006
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 77 publications
(87 citation statements)
references
References 43 publications
3
66
2
16
Order By: Relevance
“…The risk of pneumocephalus could be reduced by the immediate skin closure after cessation of spontaneous blood efflux in the 30° Trendelenburg position. This technique, though effective, was associated with acute subdural bleedings, intracerebral bleeding, subdural empyemas, and insufficient hematoma evacuation (12).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The risk of pneumocephalus could be reduced by the immediate skin closure after cessation of spontaneous blood efflux in the 30° Trendelenburg position. This technique, though effective, was associated with acute subdural bleedings, intracerebral bleeding, subdural empyemas, and insufficient hematoma evacuation (12).…”
Section: Discussionmentioning
confidence: 99%
“…Another modified bed side technique by Reinges et al was also found to be effective, which could be recommended in patients with poor general condition (12). Twist drill was performed using a 3 mm hand driven drill to penetrate the skull only.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…15,21) Twist drill craniostomy was introduced as a less invasive method for the treatment of CSDH, and is used worldwide. 13,19) The two burr-hole method is also widely used, 15,21) and was introduced to achieve sufficient irrigation, which could reduce the rate of recurrence of CSDH. 3,12) One burr-hole craniostomy with or without irrigation may be the most important surgical method and the most widely used in Japan.…”
Section: Introductionmentioning
confidence: 99%
“…7,21,23) Craniotomy is generally not performed because of the invasiveness of the procedure. Craniostomy is the main method of surgical treatment, 23) and is performed by twist drill craniostomy (diameter less than 5 mm), 6,7,13,19,23) one burr-hole craniostomy (8-15 mm), 5,7,18,20) and two burr-hole craniostomy. 15,21) Twist drill craniostomy was introduced as a less invasive method for the treatment of CSDH, and is used worldwide.…”
Section: Introductionmentioning
confidence: 99%